2021
DOI: 10.1002/chem.202100137
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Neutral Tetrafluoroethylation of Aryl Alkynes with 1,1,2,2‐Tetrafluoroethane Sulfonic Acid Leading to α‐Tetrafluoroethylated Acetophenones

Abstract: The redox‐neutral tetrafluoroethylation of alkynes with 1,1,2,2‐tetrafluroroethanesulfonic acid (TFESA) and azobis(isobutyronitrile) (AIBN) proceeds via the formation of vinyl tetrafluoroethanesulfonates followed by a radical tetrafluoroethylation. Experimental and theoretical results support an intermolecular reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Based on the result of the radical probe experiment and our previous work, 22,27,26 we show a plausible mechanism for the reaction in Figure 1. The thermal decomposition of AIBN generates isobutyronitrile radical A.…”
Section: Scheme 1 One-pot Reaction Starting From An Alkyne and Tfohsupporting
confidence: 59%
See 1 more Smart Citation
“…Based on the result of the radical probe experiment and our previous work, 22,27,26 we show a plausible mechanism for the reaction in Figure 1. The thermal decomposition of AIBN generates isobutyronitrile radical A.…”
Section: Scheme 1 One-pot Reaction Starting From An Alkyne and Tfohsupporting
confidence: 59%
“…Then, we examined the scope of the reaction toward various vinyl triflates. As vinyl triflates can undergo facile hydrolysis during column chromatography on silica gel, we attempted one-pot reactions between alkynes and trifluoromethane­sulfonic acid (TfOH) to generate the vinyl triflates in situ . For that purpose, a dichloroethane solution of terminal alkyne 1a′ and TfOH was heated at 80 °C for 1 h, before AIBN and 1-octene were added and heating at 90 °C was continued for another 3 h. The desired product was obtained in 67% yield (Scheme ).…”
mentioning
confidence: 99%
“…In 2017, we reported a radical trifluoromethylation of vinyl triflates using ketones and Tf 2 O in the presence of a base, which led to α-trifluoromethylated ketones (Scheme ). In these reactions, the vinyl triflates act as the radical acceptor and the trifluoromethyl radical source. At the same time, Yuan and Li reported a radical trifluoromethylation of vinyl triflates with AgNO 3 /(NH 4 ) 4 S 2 O 8 .…”
mentioning
confidence: 89%
“…Based on our previous work and initial experiments we would like to propose a plausible mechanism in Figure . The reaction of 1 with Tf 2 O ( 2a ) and 2,4,6-TTBP gives vinyl trifluoromethanesulfonamide 3a (first step).…”
mentioning
confidence: 99%
“…We found that triflation and trifluoromethylation reactions proceeded efficiently by simply heating the alkyne, trifluoromethanesulfonic acid, and AIBN in dichloroethane. 19 A variety of commercially available perfluoroalkanesulfonic acids can be used in this reaction. For example, 1,1,2,2-tetrafluoroethanesulfonic acid (TFESA), 20 which can be easily synthesized from tetrafluoroethylene (TFE), can be used in a tetrafluoroethylation reaction (Scheme 11).…”
Section: One-pot Reactions From Alkynesmentioning
confidence: 99%